Comparative evaluation of the performance of rice bran and cotton seed biodiesel blends in VCR diesel engine - Sundar K.; R. Udayakumar (Energy Reports, 2020)
In the country like India, it is very advantageous to use the cotton seed oil and rice bran oil as the primary source for producing the biodiesel, as India is known as the larger producer of these seeds in the universe. This current research mainly focuses on the emission and performance of the cotton seed oil and rice bran oil for the effective utilization of biodiesel. The chemical properties of rice bran, cotton seed methyl ester were established and the properties of 5%, 10%, 15% and 20% blends known as B5, B10, B15 and B20 are measured. The blends of biodiesel were evaluated at 0, 3, 6, 9 and 12 kg of load and at a compression ratio of 15, 16, 17 and 18. Engine performance test results shows that the B20 blends of MECSO (Methyl ester cotton seed oil) and MERBO (Methyl ester rice brown oil) produce slightly less BP and more BSFC values compared to diesel. B20 (MECSO and MERBO) reduces carbon monoxide emission by 18.4% and 17.5% and also hydrocarbon emission by 3.86% and 3.13% compared to diesel. B20 blends of MECSO and MERBO produce low emissions than diesel, thus these fuel blends be the replacement of diesel in the standard diesel engine to cut down the worldwide energy demand and to reduce the environmental pollution hazards.
Keywords: 330; Cotton seed oil; Rice bran oil; Variable compression ratio; Cetane number; Methyl ester cotton seed oil; Methyl ester rice bran oil; Brake thermal efficiency; Brake specific fuel consumption; Emissions